ADJACENCY PAIRS IN STARSTRUCK MOVIE - Bramantya Pradipta; Dona Rahayu Sugiharti (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2021)
In having conversation with other people, the conversation should take in a structured way. The conversation should be managed by the participants through turn-taking. This research aims to determine the turn-taking, adjacency pairs, and sequences of the characters’ conversation in the movie entitled Starstruck. Starstruck is a movie about two teenagers who fell in love. Christopher Wilde who is a pop star and teen idol, meanwhile Jessica Olson is just an ordinary girl. The story of the movie written by Barbara Johns and the movie directed by Michael Grossman. This research uses qualitative method since the data comes in form of words. The result is 9 adjacency pairs. In the adjacency pairs there are twenty preferred answers. The first one is question-answer, there are seventeen question-answer. The second one is offer-acceptance, the researcher only found one offer-acceptance. The third one is request- acceptance, there are found two request-acceptance. There are also findings about the dispreferred answer in the adjacency pairs. The first one, the researcher only found one offer-refuse. The second one there are four assertion-dissent. The third one the researcher found two suggestion-refusal.